TINJAUAN ATAS PENGAWASAN KERJA PADA PROSEDUR KEPABEANAN IMPOR EMAS - Marsanto Adi Nurcahyo; Nurul Budi Utomo (JURNAL INFO ARTHA, 2022)
Gold import activities have a significant role in international trade carried out by Indonesia. Based on value, gold is included in the top 10 commodities imported by Indonesia. This is important to ensure the implementation of import customs procedures on gold import activities. The problem in this study is how the customs process gold imports and how to supervise the work carried out in customs services. This study uses descriptive qualitative research methods. Data was obtained through in-depth interviews with stakeholders. Based on interviews, the work supervision carried out by organizational leaders is not only on gold import activities but on all activities in the office. The results of the study indicate that the Service Office within the Directorate General of Customs and Excise has carried out customs service procedures for gold imports according to the provisions. The leadership of the organization has also carried out work supervision well. Evidence of supervision activity carried out before, during, and after the activities